Regulation of human brown adipose tissue by adenosine and A2A receptors – studies with [15O]H2O and [11C]TMSX PET/CT - Minna Lahesmaa; Vesa Oikonen; Semi Helin; Pauliina Luoto; Mueez U Din; Alexander Pfeifer; Pirjo Nuutila; Kirsi A. Virtanen (Springer Berlin Heidelberg, 2022)
Purpose
Brown adipose tissue (BAT) has emerged as a potential target to combat obesity and diabetes, but novel strategies to activate BAT are needed. Adenosine and A2A receptor (A2AR) agonism activate BAT in rodents, and endogenous adenosine is released locally in BAT as a by-product of noradrenaline, but physiological data from humans is lacking. The purpose of this pilot study was to investigate the effects of exogenous adenosine on human BAT perfusion, and to determine the density of A2ARs in human BAT in vivo for the first time, using PET/CT imaging.
Methods
Healthy, lean men (n = 10) participated in PET/CT imaging with two radioligands. Perfusion of BAT, white adipose tissue (WAT) and muscle was quantified with [15O]H2O at baseline, during cold exposure and during intravenous administration of adenosine. A2AR density of the tissues was quantified with [11C]TMSX at baseline and during cold exposure.
Results
Adenosine increased the perfusion of BAT even more than cold exposure (baseline 8.3 ± 4.5, cold 19.6 ± 9.3, adenosine 28.6 ± 7.9 ml/100 g/min, p < 0.01). Distribution volume of [11C]TMSX in BAT was significantly lower during cold exposure compared to baseline. In cold, low [11C]TMSX binding coincided with high concentrations of noradrenaline.
Conclusions
Adenosine administration caused a maximal perfusion effect in human supraclavicular BAT, indicating increased oxidative metabolism. Cold exposure increased noradrenaline concentrations and decreased the density of A2AR available for radioligand binding in BAT, suggesting augmented release of endogenous adenosine. Our results show that adenosine and A2AR are relevant for activation of human BAT, and A2AR provides a future target for enhancing BAT metabolism.